The Eurasian media space in the post-global world - Nigmatullina, К.Р.; Polyakov, А.К. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2024)
The article presents a meta-analysis of sources on the problem of mediatization of Eurasian integration in the post-global space. The study showed that differences in national information policies and digital development strategies inevitably lead to the desired result – multipolarity in the media space and value media discourse. The authors answer the questions of how the processes of globalization and regional integration have influenced the formation of a unified media space in Eurasia, what factors contribute to or hinder the integration of the Eurasian media space, how digitalization affects the interaction of traditional and new media in the Eurasian media space, what challenges arise in connection with the regulation of digital platforms and online content in the context of integration.